MANAGEMENT OF WASTE FROM HEALTH CARE FACILITIES - Ahmad Mir, Ishfaq; Ahmad Dar, Shabir (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
Due to the threats to human health and the environment posed by improper waste management techniques, healthcare waste management is attracting increased attention. This study set out to analyse healthcare waste management methods in hospitals in India focusing on the risks perceived by and real dangers to healthcare workers. Three of the region's six hospitals participated in the study, representing 41% of total available beds. We gathered information by means of questionnaires, in-person interviews, and close observation. Correct waste separation was shown to be positively correlated with the frequency of interaction with the waste, suggesting that this is the most prevalent area of healthcare waste practise where improvements might be made. The healthcare employees' risk perceptions are positively correlated with the frequency of contact: they are highest for the environment (4.24) and trash workers (4.08) and lowest for patients (3.29) and visitors (2.80). The problems of the correct separation of wastes and the lack of awareness concerning the importance of that separation are related to the risk perceptions of healthcare professionals. Needle sticks and other sharps injuries are more common in direct patient care than in waste disposal, and their prevalence is directly proportional to the specific duties performed by each healthcare profession (doctors, nurses, and housekeepers). Furthermore, the management methods related to, and the perceptions of risk pertaining to, healthcare wastes appear to have been conditioned by statutory definitions and classifications of healthcare wastes.